Optional projection under equivalent local martingale measures - Francesca Biagini; Andrea Mazzon; Ari-Pekka Perkkiö (Finance and Stochastics, 2023)
We study optional projections of G-adapted strict local martingales on a smaller filtration Funder changes of equivalent martingale measures. General results are provided as well as a detailed analysis of two specific examples given by the inverse Bessel process and a class of stochastic volatility models. This analysis contributes to clarify the absence of arbitrage opportunities of market models under restricted information.
Keywords: C650; D82; 330; Local martingale; Optional projection; Local martingale measure; Filtration shrinkage